Local Wisdom and Adaptation of Traditional Fishing Communities in the Era of Modernization in Pacitan Regency - Agung Wibowo; Winarno Joko; Suwarto Suwarto; Permatasari Putri (Komunitas, 2026)
Traditional fishing communities in Pacitan Regency have social, cultural, and economic systems that have been passed down from generation to generation. The local wisdom they possess is not only related to fishing techniques and sustainable utilization of marine resources, but also includes social values, norms, and beliefs that are the basis of the life of the fishing community. However, in the era of modernization, rapid social and economic changes have brought various challenges to the sustainability of their local traditions and practices. Modernization only favors rich fishermen, while poor fishermen remain in poverty because it turns out they do not have access, especially capital, to own fishing technology that was introduced in line with modernization. Most of Indonesia's territory is ocean, however, resource management in Indonesia's coastal and marine areas is at a crossroads. Poverty, social inequality, ignorance and backwardness will continue to be inherited from generation to generation and continue throughout time as long as the development paradigm does not change. The objectives of this study are: (1) to local wisdom of traditional fishermen in Pacitan Regency; (2) to describe fishermen's adaptation strategies in facing modernization; The research method used is qualitative descriptive research, with a phenomenological research approach. Data sources include primary data and secondary data. The research was conducted from April to July 2024. Data collection techniques used: in-depth interviews, participant observation, focus group discussions, documentation studies. The results of the research show that fishermen in Sirnoboyo Village still believe in special rituals to ask sea guards for smooth sailing. Rituals and myths are fishermen's efforts to establish a good relationship with nature in the place where they earn their living. In many cases working in the marine environment is fraught with risk because fishermen's job is to hunt fish, the results cannot be determined with certainty, everything is almost speculative. The problem of risk and uncertainty occurs because the sea is an area that is considered free for exploitation. There are various adaptation strategies carried out by traditional fishermen in facing modernization, namely collective development, institutional development, diversification and empowering fishermen's wives. Therefore, the empowerment strategy carried out for fishing communities is more focused on institutional transformation.